Aplikasi Rancangan Campuran Kerja Model Superpave Untuk Sma 0/11 Dengan Bahan Pengisi Abu Terbang - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
Absract Increasing road users will effect on flow and then pavement will be more traffucked.all of those will create pavement defects rise quicker.There are many quallity parameters of pavement layeras and air voids a range of the range will be an indication of pavement defect types.which are cracking for high air void and plastic deformation for loe air voids.From this parameters pavement layers have 4 % air voids will be moderate. The Asphalt institute introduces superior performng asphalt pavement(superpave) to over come inctreasing traffic flow and pavement layewr defect.Ajob mix formula of the superpave is based on 4% air voids.To find a job mixfollowed a requirement an adjusment should be carried out on the aggregrate gradation and asphall content.Family a job mix design model is prepared .The Model will be applied on split mastic asphall of fly ash. From this research find out that the job mix design of superpave model is applicable for split matic asphalt of fly ash.air voids of the mix closed to 4 % can be established